La vegetación selvática de la región de Gómez Farías, Tamaulipas, México - Valiente-Banuet, Alfonso; Gonzalez Medrano, Francisco; Piñero Dalmau, Daniel (Instituto de Ecología, A.C., 1995)
In this work a descriptive vegetational analysis of the tropical forests, as well as of aquatic and riparian communities in the Gómez Farías municipality is presented. The study area is located in the southern part of the state of Tamaulipas in a physiographical complex of the Sierra Madre Oriental, between 100 and 900 meters above the sea level. The tropical forests were described by means of field samplings analyzing their structure and composition, whereas aquatic and riparian communities were characterized considering a floristic composition criterion. From the six vegetation types encountered in the study site, four corresponded to tropical forests, whose distribution can be associated to the effect of the microenvironmental diversity produced by physiographical heterogeneity. A previous study reported the existence of a Tropical Evergreen Forest for this part of Mexico, but our work indicates that only in areas protected by the physiography, it is possible to find this vegetation variant. Vegetation differences among sampling sites such as understorey densities, diversity levels and clumped distribution patterns of some species are associated to microenvironmental heterogeneity and possible disturbance effects of tropical storms that are common in this part of Mexico. A total of 286 species of angiosperms are reported for the zone.